The Poudre River: history of collaboration over conflict - Cech, Tom, author (Colorado State University. Libraries, 2014)
The meeting was held on a hot, dry summer day in 1874. Two groups of irrigators, from the downstream Union Colony (Greeley) and the new agricultural community in upstream Fort Collins - came armed with guns. The neutral Eaton Schoolhouse was too small to hold everyone, so people crammed the doorway. Most were Civil War veterans, and they all had a problem. "How would the two feuding groups divide the trickle of Cache la Poudre River water the remainder of the irrigation season - would it be based on "greatest need" or by priority (who dug their ditch first)?" The Union Colony delegates didn't like the greatest need idea, and they "hurled defiance in hot and unseemly language." The debate escalated with the Union Colony irrigators threatening to dig new irrigation ditches upstream of Fort Collins to choke off their water supply. The Fort Collins contingent objected to their uncooperative reaction. Then the meeting got ugly. One man, unable to bear the tension any longer, stood up and yelled, "Every man to his tent! To your rifle and cartridges!" It was a flashpoint in Colorado's water history. Were irrigators shot at this meeting? Who tried to calm the crowd and come up with a workable compromise for water management on the Cache la Poudre River? Tom Cech will explain this and more.
Presented at the Fall 2014 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Perspectives on the Poudre: Working River/Healthy River", September 9, 2014, Colorado State University, Fort Collins, Colorado. This fall semester's bi-weekly Seminar and Discussion Series focuses on the Poudre River and its watershed, its ecological needs, and how it is used to supply water for agriculture and urban needs. Presenters will highlight their topics and engage participants in dialogue. The series will culminate in a "world café" - campus and community open dialogue about the Poudre.
Tom Cech was born and raised on a farm near Clarkson, Nebraska, graduated from Kearney State College with a Bachelor of Science Degree in Math Education, and later received a Masters Degree in Community and Regional Planning from the University of Nebraska – Lincoln. He was Executive Director of the Central Colorado Water Conservancy District in Greeley, taught water undergraduate and graduate level water resources courses at the University of Northern Colorado and Colorado State University, and is now the Director of the One World One Water (OWOW) Center for Urban Water Education and Stewardship at Metropolitan State University of Denver. Tom wrote "Principles of Water Resources: History, Development, Management and Policy," published by John Wiley & Sons - currently in its 3rd edition. Tom also recently published "Introduction to Water Resources and Environmental Issues," (co-author Dr. Karrie Pennington) with Cambridge University Press, and "Colorado Water Law for Non-Lawyers," (co-author P. Andrew Jones) with the University Press of Colorado. He has also completed histories of the Colorado Water Conservation Board and the Colorado State Engineer's Office with Bill McDonald and Dick Stenzel, respectively.
Poster presentation.